Avian adenovirus infections: diversity of pathogens, hazard to poultry industry and problems of immunoprophylaxis (review) - Yu. R. Zelenskiy; M. S. Volkov; I. A. Komarov; N. V. Moroz; N. S. Mudrak; T. V. Zhbanova (Ветеринария сегодня)
The data on diversity of adenovirus pathogens in nature and the role of the main representatives of the Adenoviridae family in poultry infectious pathology are presented. Special attention is paid to problematic issues of immunoprophylaxis due to lack of cross-immunity between different virus serotypes. There is no single and effective approach in the global strategy of immunoprophylaxis of avian adenoviruses, therefore, improving the means of avian adenovirus disease control is an urgent and important task. Avian adenovirus infections are represented by different nosological units: egg drop syndrome, hydropericardium syndrome, adenoviral gizzard erosion, marbled spleen disease of pheasants, hemorrhagic enteritis of turkeys, inclusion body hepatitis and many unclassified diseases. The paper provides data on the main nosological forms of adenovirus infections that pose a threat to cost-effective poultry farming, and highlights test results obtained by foreign authors on the effectiveness of some vaccines against adenovirus infection. Most vaccines have been developed to prevent avian hydropericardium syndrome, however, occurrence of many virus serotypes requires effective means of prevention and diagnosis in order to control other infections caused by adenoviruses. There is no registered vaccine against adenovirus infections that cause inclusion body hepatitis and adenoviral gizzard erosion. At the same time, inclusion body hepatitis alone accounts for 2.9% of all recorded avian infectious diseases. Vaccines registered in the Russian Federation are not enough to fully control these infections, and that requires a timely solution to the problem. The variety of avian adenoviruses determines the problems of their differential diagnosis and specific prevention.